Novel Optical and Laser Physics Paradigms for Extreme Precision Metrology Imaging and Information Processing (Development Engineering Conferences Center Articles Database, 2025)
The increasing demand for ultra-high accuracy in measurement, imaging resolution, and information processing has pushed conventional optical and laser technologies toward their fundamental physical limits. Classical optical systems are constrained by diffraction, noise, stability issues, and limited control over light–matter interactions, which restrict their applicability in next-generation precision-driven applications. In response to these challenges, recent advances in optical and laser physics have introduced novel paradigms that enable unprecedented levels of control over optical fields in spatial, temporal, spectral, and quantum domains. This paper presents a comprehensive analytical investigation of emerging optical and laser physics paradigms and examines their potential to enable extreme precision in metrology, advanced imaging, and photonic information processing. By integrating concepts from classical, quantum, nonlinear, and ultrafast optics, the study systematically analyzes the physical mechanisms underlying structured light, coherence engineering, quantum-enhanced measurements, and engineered photonic media. A comparative analytical framework is employed to assess these paradigms in terms of sensitivity, resolution, noise suppression, scalability, and system robustness. The results highlight the transformative role of novel optical strategies in surpassing conventional performance limits and reveal unifying design principles that bridge fundamental physics and practical system implementation. The study concludes that the convergence of advanced laser dynamics and innovative optical architectures offers a viable pathway toward redefining precision standards and enabling next-generation optical technologies for scientific and technological applications.